Analysis of pathological manifestations of concrete in urban overpasses - Lima, Henrique Jorge Nery; Ribeiro, Ricardo da Silva; Melo, Guilherme Sales Soares de Azevedo; Palhares, Rodolfo de Azevedo (Revista ALCONPAT, 2019)
The paper presents the case study of pathological manifestations in concrete structures, located in the Northern Road Hub of Brasília, using the GDE / UnB methodology, which qualifies and quantifies the degradation of structural damages. The general state of the structure was characterized in order to serve as a subsidy for decision making regarding routine interventions, in order to extend the useful life of the structure. The methodological routine consists of conducting field inspections, catalog of structural pathologies with photographic survey, characterization of pathologies and classification according to the weighting factors and damage intensity factors of the structure according to the GDE / UnB methodology for special works of art, calculation and overall classification of the structure damage.